Corporate Control and the Speed of Strategic Business Unit Decision Making - Kownatzki, Maximilian; Walter, Jorge; Floyd, Steven W.; Lechner, Christoph (Academy of Management Journal, 2013)
Decision speed has long been recognized as a critical determinant of firm performance, particularly in dynamic environments. Extending prior studies, which have largely focused on firm-level decision speed in small- and medium-sized organizations, this study explores how control mechanisms set by corporate headquarters in multibusiness firms influence decision speed at the strategic business unit (SBU) level. Using a multimethod approach, we first inductively derive six types of corporate control, before deductively examining their effects on SBU-level decision speed in five international multibusiness organizations. Our results suggest that three corporate control types enhance decision speed (goal setting, extrinsic incentives, and decision process control); two have no effect (negative incentives and conflict resolution); and one has a negative effect (strategy imposition). By integrating results from our qualitative and quantitative analyses, we are also able to identify transparency/alignment, outcome orientation, participation, trust, and timely feedback as the key mechanisms accounting for these effects.